2005
DOI: 10.1073/pnas.0504599102
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific morphologies of yeast prion amyloid fibrils

Abstract: (1,2) indicates that the differences between strains must somehow be embodied in distinguishable, self-propagating structural features of the infectious amyloid fibrils formed by seeded growth in vitro with recombinant Sup35 prion protein. Induction of prion disease in transgenic mice by injection of amyloid aggregates of recombinant mouse prion protein (3) supports the hypothesis (4) that strains of the mammalian transmissible spongiform encephalopathies are caused by self-propagating misfolded forms of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 36 publications
7
115
1
1
Order By: Relevance
“…Non-integer numbers of peptides per cross-␤ repeat were also obtained for other amyloid fibrils (25). This lends support to our MPL measurements.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Non-integer numbers of peptides per cross-␤ repeat were also obtained for other amyloid fibrils (25). This lends support to our MPL measurements.…”
Section: Discussionsupporting
confidence: 74%
“…The MPL measurements were calibrated with Tobacco Mosaic Virus (TMV) for each individual image as described in ref. 25, and a cross-␤ repeat of 4.7 Å for all fibril morphologies was assumed.…”
Section: Scanning Transmission Electron Microscopy (Stem)mentioning
confidence: 99%
“…Measurements of the mass per unit length of Sup35 1-65 fibrils showed approximately one monomer per 0.47 nm in each of three variants (52). This result is inconsistent with a single-helix ␤-helical model but is consistent with an in-register parallel ␤-sheet structure with purely intermolecular backbone hydrogen bonding.…”
Section: Discussioncontrasting
confidence: 31%
“…The efficiency of their cellular propagation is kinetically determined where the fastest multiplicating, truebreeding structures dominate. We previously suggested that the cellular frangibility of prion fibers played an important role in determining the strength of a prion strain (14). This notion was born out by a beautiful full treatment in Tanaka (Fig.…”
Section: Resultsmentioning
confidence: 99%